2001
DOI: 10.1002/jnr.1207
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin treatment decreases mononuclear cell infiltration into the CNS of Lewis rats with experimental allergic encephalomyelitis

Abstract: Mononuclear cell infiltration into the CNS and induction of inflammatory cytokines and iNOS in diseases like multiple sclerosis (MS) and experimental allergic encephalomyelitis (EAE) have been implicated in subsequent disease pathogenesis and progression. We report that Lovastatin treatment blocks the clinical disease and induction of inflammatory cytokines and iNOS in spinal cords of MBP induced EAE rats. A significant number of the infiltrating cells in CNS were ED1+ cells of monocyte/macrophage lineage. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
100
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(106 citation statements)
references
References 31 publications
5
100
0
1
Order By: Relevance
“…The severity of histologic neural tissue lesions clearly correlated with these clinical symptoms. Cervical spinal cord sections showed typical and abundant inflammatory foci, localized around small vessels, similar to many research reports (Stanislaus et al 2001). Differing from these results, animals from Botucatu colony immunized in similar conditions, displayed a very low susceptibility to EAE development.…”
Section: Discussionsupporting
confidence: 88%
“…The severity of histologic neural tissue lesions clearly correlated with these clinical symptoms. Cervical spinal cord sections showed typical and abundant inflammatory foci, localized around small vessels, similar to many research reports (Stanislaus et al 2001). Differing from these results, animals from Botucatu colony immunized in similar conditions, displayed a very low susceptibility to EAE development.…”
Section: Discussionsupporting
confidence: 88%
“…We expected a decrease in the level of inflammatory infiltration during the remission phase because established data have shown that inflammatory cells strongly contribute to the pathology of this disease (Man et al 2007). In addition, experimental therapeutic strategies have demonstrated a clear correlation between clinical remission and the prevention of mononuclear cell transmigration to the spinal cord (Stanislaus et al 2001). Encephalitogenic T cells undergo apoptosis during the remission phase, which may lead to a decrease in inflammatory infiltrate with- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, lovastatin has been shown to inhibit the induction of inducible nitric oxide synthase and proinflammatory cytokines in rat astrocytes, microglia and macrophages [2] and to repress MHC-II mediated T-cell activation [3]. Moreover, lovastatin treatment decreased neuroinflammatory activity and clinical signs in experimental allergic encephalomyelitis, an animal model for multiple sclerosis (MS) [4]. On the basis of these findings we have begun to investigate whether lovastatin could be a treatment option for MS patients.…”
mentioning
confidence: 99%